Experimental research of a dual-beam compressive-mode piezoelectric energy harvester. Issue 1 (1st February 2023) - Li, Zhongjie; Peng, Xuzhang; Gong, Ying; Zhu, Chuan; Zhang, Lan; Peng, Yan
Abstract: In this article, we present a dual-beam compressive-mode piezoelectric energy harvester (DC-PEH). The DC-PEH is made up of a force amplifier, a piezoelectric stack, and a pair of symmetrically arranged cantilever-mass systems, supported by a base that is fixed on a rod. A two-stage force amplification mechanism of the DC-PEH is realized by coupling the elastic beams with the force amplifier. We first established a force analysis to describe the two-stage force amplification effect of the DC-PEH. Furthermore, a prototype has been fabricated and we carried out a series of experiments. We examined the open-circuit voltage and working bandwidth of the DC-PEH to verify the two-stage force amplification effect under different accelerations. Moreover, a parametric study was performed to investigate the influence of structure parameters on the output performance of the DC-PEH. We conducted the frequency sweep response and power output comparisons with different lengths of beams and different masses.